DIMENSI RESPONSIVENESS DAN ASSURANCE KEPUASAN IBU HAMIL TERHADAP PELAYANAN BIDAN: IMPORTANCE -PERFORMANCE ANALISIS - Juariah Juariah (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2021)
Health workers who provide obstetric and neonatal services, especially midwives, must be capable and skilled in providing services in accordance with established standards. Improving the quality of maternal and child health services provided by midwives is expected to reduce morbidity and mortality. Low patient satisfaction will have an impact on the number of visits to midwives. Service standards determine the quality of public health services and are very influential on the level of patient satisfaction. The purpose of this study is to analyze the level of patient satisfaction with midwife services from the dimensions of responsivity and the dimension of Assurance. The research method uses a survey approach. Primary data were obtained using a questionnaire for 52 pregnant women conduct pregnancy checks at the Puskesmas obtained by purposive sampling technique. Bivariate analysis uses the mann whitney test and Importance-Performance analysis. The results of the study indicate that the patient feels less satisfied with the Responsiveness dimension. And according to the Cartesian diagram analysis it can be seen that there is one aspect that is the top priority of the improvement program, namely in the midwife aspect providing clear and easy to understand information The quality of health services is not only supported by physical facilities but the attitudes and communication of health workers, midwives in providing services are also an important part of service so that patients feel comfortable. Thus it is hoped that there will be training on quality communication and services for health workers.